1984
DOI: 10.1139/v84-005
|View full text |Cite
|
Sign up to set email alerts
|

Complexes des ions Hg2+ avec Le monomère et le dimère de la thymine: 5-methyl-2,4 (1H, 3H) pyrimidinedione

Abstract: M. M. PETIT-RAMEL, G. THOMAS-DAVID, G. PERICHET et P. POUYET. Can. J. Chem. 62, 22 (1984). Les constantes d'association relatives aux complexes des ions Hg2' avec les formes monomkre (TM) et dimkre (TD) de la thymine sont calculCes a partir de mesures protomCtriques effectuCes dans un large domaine de pH: 2 < pH < 11. Le traitement des donnCes de chacun des systkmes est conduit par une mtthode de pit-mapping et l'on peut donner la ripartition des diverses espkces complexes en fonction du pH.En ce qui conceme l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
2
4
0
1
Order By: Relevance
“…So these atoms do not have the same value z (Table 8). These results were consolidated by works of Petit-Ramel et al (1984) and Boungou et al (1989).…”
Section: 2b Structural Aspectmentioning
confidence: 79%
See 2 more Smart Citations
“…So these atoms do not have the same value z (Table 8). These results were consolidated by works of Petit-Ramel et al (1984) and Boungou et al (1989).…”
Section: 2b Structural Aspectmentioning
confidence: 79%
“…Experimental data were computed by use of the NEWSI and NEWMI programs derived from the LETRAGROP program (Sillen et al, 1964) used and cited by Martin et al (1971) which was modified and tested in our laboratory to study number of various equilibrium (Petit-Ramel et al, 1984;M'Boungou et al, 1989). These programs make possible the refinement of the parameters by juxtaposition of a least square method and a pit-mapping method the principles of which are now briefly outlined.…”
Section: Data Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Les bases puriques et pyrirnidiques rnonomkres cornposant des acides nuclgiques sont susceptibles de cornplexer de nombreux cations tels que H~~+ , Pt2+, Cu2+, ~i~+ , z n 2 + , c o 2 + , Mg2+, Ca2+ et Pb2+ bien que les constantes de stabilite correspondantes ne soient pas calculCes (1,2,(5)(6)(7)(8). Excepte les travaux que notre laboratoire a publies nous n'avons repertori6 aucune donnCe bibliographique relative a la deprotonation et aux stabilitts thermodynarniques de ces rn&rnes bases sous forme dimCrisCe.…”
Section: Resultatsunclassified
“…Although it has been suggested that interaction of these metal ions could enhance the DNA conductivity, details of the mechanism are still unclear, since exact coordination sites of the ions in DNA have not been determined. In this regard, mercury (II) ions (Hg 2+ ) preferentially bind to thymine-thymine (TT) mismatch base pairs, in which imino protons of the bases are replaced by Hg 2+ , and generate stable non-hydrogen-bonding base pairs [12][13][14]. Based on the preferential bindings of Hg 2+ to a TT site and of Ag + to a cytosinecytosine (CC) site, novel nanoscale sensors have been developed recently [15,16].…”
mentioning
confidence: 99%